Formation and characterization of solid fat mimetic based on pea protein isolate/polysaccharide emulsion gels - Hou, Wenbo; Long, Jie; Hua, Yufei; Chen, Yeming; Kong, Xiangzhen; Zhang, Caimeng; Li, Xingfei (Frontiers in Nutrition, 2022)
The emulsion gels that can be used as solid fat replacers were produced with different polysaccharides (κ-carrageenan, κC; high-acyl gellan, HA; konjac glucomannanon, KGM), pea protein isolate (PPI) and sunflower seed oil. The effect of polysaccharide concentration on the texture, rheological property, microstructure, and water holding capacity of the mixed emulsion gels were investigated. Rheological results showed that the presence of polysaccharides enhanced the hardness, storage modulus and resistance against deformation of emulsion gel, where PPI/κC system exhibited superior hardness with a similar level of pig back fat, due to the self-gelation behavior of κC. CLSM and SEM results showed that the presence of κC, HA, and KGM broke the uniform structure of gel network and formed irregular, threadlike, and oval shaped inclusions respectively, resulting in the broken and coalescence of oil droplets. The α-helix content of emulsion gels decreased, while β-sheet, β-turn and random coils slightly increased due to the unfolding of protein during gel formation. This study may offer a valuable strategy for the development of solid fat mimetic with the characteristics closing to the pig back fat